OŚWIADCZENIA ‘PRO FUTURO’ ‒ DYLEMATY PRAWNE - Pacian, Jolanta (Zeszyty Prawnicze, 2016)
Advance Directives: Legal Dilemmas Summary The experience of the European countries and the U.S. has shown that, although in practice the use of advance statements is giving rise to problems for healthcare professionals and patients alike, both legal and medical in nature, they are undoubtedly a manifestation of patients’ independence and a sign of respect for their wishes when life or health is at stake. The regulations regarding the introduction of the living will into the Polish legal framework should take into account the patient’s choice only with regard to preferred methods of treatment in the event of his loss of consciousness and inability to inform the physician of his preferences of treatment.